Composition and spray device

A composition of fine cellulose fibers with sulfate ester groups addresses safety concerns of strong acids by enhancing dispersibility and stability, offering a safer and effective cleaning solution.

JP2025016347APending Publication Date: 2025-01-31MUSHUGEN IND +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2024090353
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-07-21
Filing Date
2024-06-04
Publication Date
2025-01-31

AI Technical Summary

Technical Problem

Existing cleaning compositions containing strong acids like hydrochloric acid and sulfamic acid pose safety risks due to adverse human health effects, and there is a need for a safer and environmentally friendly alternative.

Method used

A composition comprising fine cellulose fibers with sulfate ester groups is developed, which enhances dispersibility and stability, allowing for safe and effective use in spray devices.

Benefits of technology

The composition provides high safety and effective cleaning performance, reducing the risk of accidents and environmental impact while maintaining cleaning efficacy.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025016347000012
    Figure 2025016347000012
  • Figure 2025016347000013
    Figure 2025016347000013
  • Figure 2025016347000014
    Figure 2025016347000014
Patent Text Reader

Abstract

To provide a composition characterized by high safety and suitability for spraying with a spray device.SOLUTION: A composition according to the present invention contains fine cellulose fibers and water. At least some of hydroxy groups in the fine cellulose fibers are substituted with sulfate ester groups.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a composition and a spray device. [Background technology]

[0002] 2. Description of the Related Art Conventionally, liquid compositions containing strong acids such as hydrochloric acid and sulfamic acid, chlorine bleaching agents, and the like have been used for cleaning toilets and the like.

[0003] It is also known to add a thickener such as polyethylene glycol, polyalkylene oxide, or polyvinyl alcohol to a spray composition (see, for example, Patent Documents 1 and 2). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Patent Publication No. 2022-78252 [Patent Document 2] JP 2022-88549 A Summary of the Invention [Problem to be solved by the invention]

[0005] However, strong acids such as hydrochloric acid and sulfamic acid, and chlorine bleaching agents have safety issues such as adverse effects on the human body, and there is a risk of accidents when handled by people with little knowledge of chemicals. In addition, thickeners such as polyethylene glycol are not very safe or environmentally friendly.

[0006] Therefore, an object of the present invention is to provide a composition which is highly safe and can be sprayed using a spray device. [Means for solving the problem]

[0007] In order to achieve the above object, the composition of the present invention comprises: Contains fine cellulose fibers and water, At least a portion of the hydroxyl groups of the fine cellulose fibers is substituted with sulfate ester groups. Effect of the Invention

[0008] According to the present invention, by using the above-mentioned specified fine cellulose fibers, it is possible to provide a composition which is highly safe and can be sprayed using a spray device. [Brief description of the drawings]

[0009] [Figure 1] FIG. 1 is a photograph showing the results of an antifouling performance confirmation test in the examples. [Diagram 2] FIG. 2 is another photograph showing the results of the antifouling performance confirmation test in the examples. [Diagram 3] FIG. 3 is a photograph showing the results of a dripping test in the examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] [Embodiment 1: Composition] The composition of the present invention contains fine cellulose fibers and water.

[0011] (Microfine cellulose fiber) The fine cellulose fibers have at least a part of their hydroxyl groups substituted with sulfate ester groups. Specifically, the fine cellulose fibers have at least a part of the hydroxyl groups (-OH groups) of the cellulose (a chain-like polymer in which D-glucose is bonded via β(1→4) glucoside bonds) constituting the fibers substituted with sulfate ester groups represented by formula (1).

[0012] (-OSO3 - ) r Z r+ (1) In formula (1), r is an independent natural number from 1 to 7, Z r+When r=1, it is at least one selected from the group consisting of a hydrogen ion, an alkali metal ion, a monovalent transition metal ion, an ammonium ion, an aliphatic ammonium ion, an aromatic ammonium ion, and a cationic polymer, and when r=2 or more, it is at least one selected from the group consisting of an alkaline earth metal ion, a polyvalent metal ion, and a compound containing two or more cationic functional groups (e.g., diamine, etc.) in the molecule.

[0013] The fine cellulose fibers have improved hydrophilicity due to the incorporation of sulfate ester groups. As a result, the fine cellulose fibers have improved dispersibility when dispersed in the composition. Furthermore, the electronic repulsion of the introduced sulfate ester groups makes it easier to maintain the dispersion state in the composition.

[0014] The amount of sulfate ester groups introduced into the fine cellulose fibers can be expressed as the amount of sulfur introduced based on the sulfate ester groups. The amount of sulfur introduced per 1 g (mass) of the fine cellulose fibers is, for example, higher than 0.4 mmol / g, 0.42 mmol / g to 9.9 mmol / g, 0.5 mmol / g to 9.9 mmol / g, or 0.6 mmol / g to 9.9 mmol / g.

[0015] If the amount of sulfur incorporated is more than 0.42 mmol / g, the hydrogen bonds between the fibers do not become too strong, and the dispersibility in the composition tends to improve, and if it is 0.5 mmol / g or more, the electronic repulsion can be made stronger, making it easier to maintain a stable dispersion state. On the other hand, if the amount of sulfur incorporated is 9.9 mmol / g or less, the decrease in crystallinity and the increase in cost when introducing sulfur can be suppressed.

[0016] In particular, when attention is paid to maintaining dispersibility, the amount of sulfur introduced is, for example, more than 0.42 mmol / g and not more than 3 mmol / g, 0.5 mmol / g to 3 mmol / g, 0.5 mmol / g to 2 mmol / g, or 0.5 mmol / g to 1.5 mmol / g.

[0017] The amount of sulfur introduced into the fine cellulose fibers (i.e., the amount of sulfate ester groups introduced) can be measured, for example, by using a CHNS / O elemental analyzer. The amount of sulfur introduced can also be calculated, for example, by measuring electrical conductivity.

[0018] The average fiber length of the fine cellulose fibers can be indirectly expressed, for example, by the degree of polymerization. The average fiber length of the fine cellulose fibers is, for example, 280 or more, 300 to 1000, or 300 to 600 in terms of the degree of polymerization.

[0019] When the degree of polymerization of the fine cellulose fibers is 280 or more, it is possible to suppress weakening of fiber entanglement due to a decrease in fiber length. On the other hand, when the degree of polymerization of the fine cellulose fibers is 600 or less, the dispersibility in the composition tends to be high.

[0020] The method for measuring the degree of polymerization is not particularly limited, but for example, a copper ethylenediamine method can be used. Specifically, the degree of polymerization of the fine cellulose can be measured by dissolving the fine cellulose fibers in a 0.5 M copper ethylenediamine solution and measuring the viscosity of the solution by a viscometer.

[0021] The average fiber width of the fine cellulose fibers is not particularly limited, but is, for example, 1 nm to 1000 nm, 2 nm to 500 nm, 2 nm to 100 nm, 2 nm to 30 nm, or 2 nm to 20 nm when observed with an electron microscope.

[0022] The average fiber width of the fine cellulose fibers can be measured using a known technique. For example, fine cellulose fibers are dispersed in a dispersion medium such as pure water to prepare a dispersion liquid with a predetermined mass %. Then, this dispersion liquid is spin-coated on a silica substrate coated with PEI (polyethyleneimine), and the fine cellulose fibers on the silica substrate are observed. For example, a scanning probe microscope (for example, SPM9700 manufactured by Shimadzu Corporation) can be used as an observation method. Twenty fine cellulose fibers are randomly selected from the obtained observation image, and the fiber width of each fiber is measured and averaged to obtain the average fiber width of the fine cellulose.

[0023] The method for preparing the fine cellulose fibers is not particularly limited, but for example, the fine cellulose fibers can be prepared from pulp into which sulfate ester groups have been introduced (hereinafter referred to as "sulfate ester group-introduced pulp") by the method shown below. In the present invention, the "sulfate ester group-introduced pulp" refers to a fibrous member in which a plurality of cellulose fibers are assembled, and at least a portion of the hydroxyl groups (-OH groups) of the cellulose (a chain-like polymer in which D-glucose is bonded via β(1→4) glucoside) constituting the cellulose fibers contained therein are substituted with sulfate ester groups.

[0024] The fine cellulose fibers can be prepared by directly subjecting a fiber raw material to a microfibrillation treatment to obtain fine cellulose fibers and then substituting at least a part of the hydroxyl groups of the cellulose constituting the fine cellulose fibers with sulfate ester groups, or by microfibrillating sulfate ester group-introduced pulp as described below. The latter method has the advantage that the fine cellulose fibers can be prepared simply by carrying out a microfibrillation treatment step.

[0025] The sulfate ester group-introduced pulp can be obtained, for example, by the method shown below, but is not limited to this method.

[0026] In summary, this method involves subjecting a cellulose-containing fiber raw material (e.g., wood-based pulp (hereinafter simply referred to as "wood pulp")) to a chemical treatment to prepare sulfate ester group-introduced pulp. This chemical treatment step includes a contact step in which the fiber raw material is contacted with a sulfate ester group-donor compound described below and urea or a urea derivative (hereinafter referred to as "urea, etc." Examples of the urea derivative include thiourea, biuret, phenylurea, benzylurea, dimethylurea, diethylurea, tetramethylurea, benzoleinurea, and hydantoin, and one type may be used alone or two or more types may be used in combination), and a reaction step in which the fiber raw material after this contact step is subjected to a heating reaction to substitute at least a portion of the hydroxyl groups of cellulose with sulfate ester groups.

[0027] In this specification, the fiber raw material refers to fibrous pulp containing cellulose molecules. Pulp is a fibrous member in which a plurality of cellulose fibers are assembled. The cellulose fiber is an assembly of a plurality of fine fibers (e.g., microfibrils, etc.). The fine fiber is an assembly of a plurality of cellulose molecules (hereinafter, sometimes simply referred to as "cellulose"), which are chain-like polymers in which D-glucose is bonded by β(1→4) glucoside. In addition, it is preferable to wash the fiber raw material in advance. For example, by filtering and dehydrating the material using water on a 200 mesh or 235 mesh sieve, it is possible to sieve out fine fibers and debris that are too fine, which is desirable because it improves the handling during preparation. In other words, pulp is an assembly of cellulose fibers that can become residues of 200 mesh or 235 mesh.

[0028] The fiber raw material used in this method is not particularly limited as long as it contains cellulose as described above, and for example, what is generally called pulp may be used, or what contains cellulose isolated from sea squirts, seaweed, etc., and any material may be used as long as it is composed of cellulose molecules. Examples of the pulp include, but are not limited to, cotton-based pulps such as wood pulp, dissolving pulp, and cotton linter, non-wood-based pulps such as straw, bagasse, paper mulberry, mitsumata, hemp, kenaf, and fruit, and waste paper pulps prepared from waste newspapers, waste magazines, waste cardboard, etc. Note that wood pulp is easy to use as a fiber raw material from the viewpoint of ease of availability.

[0029] There are various kinds of wood pulp, but the use is not particularly limited, and examples thereof include paper pulp such as softwood kraft pulp (NBKP), hardwood kraft pulp (LBKP), thermomechanical pulp (TMP), etc. When the pulp is used as a fiber raw material, one type of pulp may be used alone, or two or more types of pulp may be used in combination.

[0030] As described above, the fine cellulose fibers are derived from natural materials, and are therefore highly safe and environmentally friendly.

[0031] The sulfate ester group donating compound is not particularly limited as long as it is a compound capable of donating sulfate ester groups to fiber raw materials, and examples thereof include sulfamic acid, sulfamic acid salts, and sulfuryl compounds having a sulfonyl group with two oxygen atoms covalently bonded to sulfur, and these compounds may be used alone or in combination of two or more. The sulfate ester group donating compound is preferably sulfamic acid, since it has a lower acidity than sulfuric acid and has a higher efficiency of introducing sulfate ester groups, is inexpensive, and is highly safe. Hereinafter, an example will be described in which sulfamic acid is used as the sulfate ester group donating compound and urea is used as the urea.

[0032] <Contact process> The contact step is a step of contacting a fiber raw material containing cellulose with sulfamic acid and urea. This contact step is not particularly limited as long as it is a method that can cause the contact. For example, the fiber raw material may be immersed in a reaction solution in which sulfamic acid and urea are dissolved in a solvent to impregnate the fiber raw material with the reaction solution, or the reaction solution may be applied to the fiber raw material, or sulfamic acid and urea may be separately applied to, impregnated into, or sprayed onto the fiber raw material. Among these, if a method of immersing the fiber raw material in the reaction solution to impregnate the fiber raw material with the reaction solution is used, sulfamic acid and urea can be contacted uniformly with the fiber raw material.

[0033] The solvent for dissolving sulfamic acid and urea is not particularly limited, and examples thereof include protic polar solvents such as water, ethanol, methanol, acetic acid, formic acid, 2-propanol, nitromethane, and aqueous ammonia, aprotic polar solvents such as acetone, ethyl acetate, tetrahydrofuran (THF), dimethylformamide (DMF), acetonitrile, dimethyl sulfoxide (DMSO), dimethyl sulfide (DMS), and dimethylacetamide (DMA), and non-polar solvents such as diethyl ether, benzene, toluene, hexane, chloroform, and 1,4-dioxane. The solvent may be used alone or in combination of two or more. In particular, water is preferred from the viewpoint of easily dissolving sulfamic acid and urea.

[0034] In addition, the fiber raw material that has been brought into contact with sulfamic acid and urea through this contacting step is sometimes called "reaction liquid-impregnated fiber."

[0035] <Contact amount of reaction solution> In contacting the fiber raw material with the reaction solution, it is preferable to make the sulfamic acid and urea in the reaction solution have a predetermined ratio relative to the fiber raw material. Specifically, the reaction solution is contacted so that the amount of sulfamic acid and the amount of urea in the reaction solution are appropriate relative to the fiber raw material in the reaction solution-impregnated fiber to be subjected to the reaction step. More specifically, the contact amount of sulfamic acid relative to the fiber raw material (solid mass, which is the dry mass) in the reaction solution-impregnated fiber immediately before being subjected to the heating reaction in the reaction step is adjusted to be equal to or greater than the contact amount of urea.

[0036] For example, the reaction liquid is prepared so that the mixing ratio of sulfamic acid and urea, in terms of mass ratio, is such that the value obtained by dividing the mass parts of sulfamic acid per 100 mass parts of solid content of the fiber raw material in the reaction liquid-impregnated fiber immediately before being subjected to the heating reaction by the mass parts of urea per 100 mass parts of solid content of the fiber raw material in the reaction liquid-impregnated fiber immediately before being subjected to the heating reaction (sulfamic acid / urea) is 0.8 or more, 0.85 or more, or 1 or more.

[0037] Also, for example, the contact amount of sulfamic acid is adjusted to be 70 parts by mass or more, 100 parts by mass or more, or 200 parts by mass or more per 100 parts by mass of the solid content of the fiber raw material in the reaction liquid-impregnated fiber immediately before being subjected to the heating reaction.

[0038] For example, the contact amount of urea, i.e., the contact amount of urea relative to the mass of solid content of the fiber raw material in the reaction liquid-impregnated fiber immediately before being subjected to the heating reaction, is adjusted to 20 parts by mass or more, 30 parts by mass or more, or 50 parts by mass or more relative to 100 parts by mass of solid content of the fiber raw material while maintaining the above-mentioned relationship with sulfamic acid. The upper limit of the contact amount of urea is not particularly limited, but is, for example, 350 parts by mass or less, 300 parts by mass or less, or 250 parts by mass or less relative to 100 parts by mass of solid content of the fiber raw material.

[0039] The contact amounts of sulfamic acid and urea per 100 parts by mass of the solid content of the fiber raw material can be appropriately calculated depending on, for example, the state of the reaction liquid-impregnated fiber to be subjected to the reaction step.

[0040] <State of fiber impregnated with reaction liquid> The state of the reaction liquid-impregnated fiber to be subjected to the above-mentioned next reaction step may be, for example, the reaction liquid-impregnated fiber as it is, i.e., a state in which the fiber raw material is in contact with the reaction liquid without actively removing water, or a state in which the fiber raw material is in contact with the reaction liquid and the water has been actively removed, etc.

[0041] The former reaction liquid-impregnated fibers (in a state where water is not actively removed) include fibers in a state where the fiber raw material is in contact with the reaction liquid (including, for example, a slurry state, etc.), and fibers prepared by removing the fiber raw material from the state where the reaction liquid is in contact with the fiber raw material and leaving it to stand.

[0042] On the other hand, the latter reaction liquid-impregnated fiber (in a state where moisture has been actively removed) refers to a fiber in which moisture has been intentionally removed from a state where the fiber raw material is in contact with the reaction liquid. For example, it includes a fiber prepared by removing the fiber raw material from the state where the reaction liquid is in contact with the fiber raw material and naturally drying it by air drying or the like, a fiber prepared by filtering and dehydrating the fiber raw material in a state where the reaction liquid is in contact with the fiber raw material, a fiber prepared by further air drying the filtered and dehydrated material, a fiber prepared by further drying the filtered and dehydrated material using a circulating air dryer, a fiber prepared by further drying the filtered and dehydrated material using a heating dryer, a fiber prepared by drying the fiber raw material in a state where the reaction liquid is in contact with the fiber raw material using a circulating air dryer or a heating dryer, and the like.

[0043] In this way, the reaction liquid-impregnated fiber to be subjected to the reaction step may be one that has not been subjected to the active water removal as described above, or one that has been actively removed to remove a certain amount of water. In addition, when removing water by drying, there is no particular problem even if the moisture content after drying is about 1%. In particular, by using the latter method, the moisture content in the reaction liquid-impregnated fiber to be subjected to the reaction step can be reduced, so that the reaction time in the heating reaction in the reaction step can be shortened. This has the advantage of improving the productivity of the sulfate ester group-introduced pulp. In addition, by using the method of performing a dehydration treatment, there is the advantage that the reaction liquid-impregnated fiber can be prepared more efficiently than when a large amount of reaction liquid is treated.

[0044] When an active drying method is used, the moisture content of the reaction solution-impregnated fibers may be reduced to about 1%, or the moisture may be removed by drying the fibers to an absolutely dry state with a moisture content significantly lower than 1%.

[0045] In this specification, the term "wet state" refers to a fiber that is impregnated with the reaction liquid and has a moisture content of 1% or more, and is not in an absolute dry state. For example, the term "wet state" may refer to fibers that are impregnated with the reaction liquid, fibers that have been dehydrated to a certain extent, and fibers that have been dried to a certain extent.

[0046] In addition, in this specification, bone dry means a state in which the moisture content is reduced to less than 1% by, for example, reducing the pressure in a desiccator containing a desiccant such as calcium chloride or diphosphorus pentoxide, or by subjecting the material to a long-term heat drying treatment.

[0047] Therefore, when the latter method described above (a reaction method in a state where active moisture removal has been performed) is used in the contact step, a method for bringing the moisture content of the reaction liquid-impregnated fiber to a non-absolutely dry state may be used, or a method for bringing the moisture content to an absolute dry state may be used, but it is preferable to use a method for bringing the moisture content to a non-absolutely dry state.

[0048] In this specification, the moisture content of the reaction liquid-impregnated fiber is calculated using the following formula. Moisture content of fiber impregnated with reaction liquid (%) = 100 - (mass of solid content of fiber impregnated with reaction liquid (g) / mass of fiber impregnated with reaction liquid at the time of moisture content measurement (g)) x 100 = {(mass of fiber impregnated with reaction liquid at the time of moisture content measurement (g) - mass of solid content of fiber impregnated with reaction liquid (g)) / mass of fiber impregnated with reaction liquid at the time of moisture content measurement (g)} x 100

[0049] The solid content mass (g) of the reaction liquid-impregnated fiber in the above formula refers to the dry mass of the reaction liquid-impregnated fiber. Specifically, it refers to the dry mass adjusted to a constant weight by drying the sample using a dryer or the like. For example, by putting the reaction liquid-impregnated fiber in a dryer and drying it under a specified drying condition (for example, a temperature of 105°C for 2 hours) and measuring the mass, the mass of the dried product after the moisture is removed from the reaction liquid-impregnated fiber (i.e., the mass of the product that is not removed under the drying condition. For example, the mass of the product containing the fiber raw material and the reagent in the reaction liquid) can be calculated. In addition, the constant weight means a state in which the moisture in the atmosphere in the treatment facility and the moisture in the raw material do not appear to enter or leave the facility. Specifically, it means a state in which the change in the mass between two consecutive measurements after drying for a certain period of time (for example, 2 hours) is within 1% of the mass at the start of drying (however, the second mass measurement should be more than half the drying time required for the first measurement).

[0050] The state of the fiber raw material when it is brought into contact with the reaction liquid is not particularly limited, and may be, for example, in a dry state or a wet state (i.e., a moist state).

[0051] <Pre-drying process in the contact process> In the above example, the method for preparing the reaction liquid-impregnated fiber in the contact step was described, in which the reaction liquid-impregnated fiber is prepared by actively removing water. When using a method for removing water while heating (pre-drying step) in this method (for example, when directly heating and drying the fiber raw material in the contact state with the reaction liquid, or heating and drying the dehydrated fiber), it is desirable to adjust the heating temperature to a predetermined temperature or lower. The drying temperature in this pre-drying step is not particularly limited, but is preferably adjusted to a temperature at which the water contained in the reaction liquid-impregnated fiber and the surrounding water can be removed and the reaction does not proceed. For example, the drying temperature in the pre-drying step can be adjusted so that the ambient temperature of the reaction liquid-impregnated fiber is 100°C or lower. On the other hand, from the viewpoint of workability, it is preferable to adjust the temperature to 50°C or higher. Therefore, the drying temperature in the pre-drying step in the contact step is preferably 50°C to 100°C, 70°C to 100°C.

[0052] <Moisture adjustment process during contact process> The contact step may include a moisture adjustment step in which the moisture content of the fiber raw material to be contacted with the reaction liquid is adjusted to fall within a predetermined range. This moisture adjustment step is a step in which the fiber raw material is adjusted by drying or humidifying so that the moisture content is a predetermined value. By including this moisture adjustment step, the moisture content in the fiber raw material when it is contacted with the reaction liquid can be made somewhat uniform, which may improve product stability in continuous operation. In addition, there is an advantage in that storage properties can be improved by drying the fiber raw material to a certain degree to reduce the moisture content (for example, the moisture content is 1% to 10%).

[0053] <Reaction process> As described above, the reaction liquid-impregnated fiber prepared in the contact step is subjected to the next reaction step. This reaction step is a step in which the cellulose fiber contained in the fiber raw material in the reaction liquid-impregnated fiber provided from the contact step is reacted with sulfamic acid and urea to replace at least a part of the hydroxyl groups in the cellulose fiber with sulfate ester groups, thereby introducing sulfate ester groups into the cellulose fiber contained in the fiber raw material. That is, this reaction step is a step in which a reaction is carried out to replace at least a part of the hydroxyl groups in the cellulose fiber contained in the reaction liquid-impregnated fiber with sulfate ester groups.

[0054] This reaction step is not particularly limited as long as it is a method capable of replacing at least a part of the hydroxyl groups of the cellulose fibers in the reaction solution-impregnated fibers with sulfate ester groups, and for example, a method of promoting the reaction by heating the reaction solution-impregnated fibers can be used. Hereinafter, the reaction will be described by taking the case where the reaction is carried out by this heating method as an example.

[0055] <Reaction temperature in the reaction process> The reaction temperature in the reaction step is not particularly limited, but is preferably a temperature at which sulfate ester groups can be introduced into the cellulose fibers constituting the fiber raw material while suppressing thermal decomposition and hydrolysis of the fibers. For example, the atmospheric temperature of the reaction liquid-impregnated fibers subjected to the reaction step is adjusted to 100°C to 200°C, 120°C to 200°C, 120°C to 180°C, or 120°C to 160°C. If the atmospheric temperature during heating is 200°C or less, thermal decomposition and discoloration of the fibers can be suppressed.

[0056] The heater or the like used in the reaction step is not particularly limited, and may be, for example, one capable of directly or indirectly heating the reaction liquid-impregnated fiber after the contact step while satisfying the above-mentioned requirements, and may be a known dryer, reduced pressure dryer, microwave heating device, autoclave, infrared heating device, hot pressing method using a heat press machine (e.g., AH-2003C manufactured by AS ONE Co., Ltd.), etc. In particular, from the viewpoint of operability, it is preferable to use a circulating air dryer since gas may be generated in the reaction step.

[0057] <Reaction time in the reaction process> The heating time (i.e., reaction time) when the heating method is used as the reaction step is not particularly limited, but is, for example, 1 minute or more, 5 minutes or more, 10 minutes or more, or 15 minutes or more when the reaction temperature is adjusted to be within the above range, and from the viewpoints of operability and cost, it is 5 minutes to 300 minutes, or 5 minutes to 120 minutes.

[0058] By carrying out the above steps, a pulp having sulfate ester groups introduced therein can be prepared.

[0059] <Cleaning process after reaction process> The reaction step may be followed by a washing step in which the sulfate ester group-introduced pulp is washed. The sulfate ester group-introduced pulp has an acidic surface due to the effect of sulfamic acid (sulfate ester group-donating compound). In addition, unreacted reaction liquid is still present. For this reason, if a washing step is provided in which the reaction is completely terminated and excess reaction liquid is removed to make the pulp neutral, the handling properties can be improved.

[0060] This washing step is not particularly limited, and may be any step that can make the sulfate ester group-introduced pulp nearly neutral. For example, a method of washing the sulfate ester group-introduced pulp with pure water or the like until it becomes neutral may be used. Neutralization washing may also be performed using an alkaline solution or the like. When performing such neutralization washing, examples of the alkaline compound contained in the alkaline solution include inorganic alkaline compounds and organic alkaline compounds. Examples of the inorganic alkaline compounds include hydroxides, carbonates, and phosphates of alkali metals. Examples of the organic alkaline compounds include ammonia, aliphatic amines, aromatic amines, aliphatic ammonium, aromatic ammonium, heterocyclic compounds, and hydroxides of heterocyclic compounds.

[0061] The method for separating the sulfate ester group-introduced pulp in the washing step is not particularly limited, and may be, for example, by filtering the sulfate ester group-introduced pulp and the washing water. For example, the sulfate ester group-introduced pulp after the reaction may be washed using a stainless steel sieve with an opening size of 243 μm (70 mesh) to 20 μm (635 mesh), 132 μm (120 mesh) to 45 μm (300 mesh), or 75 μm (200 mesh) to 45 μm (300 mesh).

[0062] <Physical properties of sulfate ester group-introduced pulp> The physical properties of the sulfate ester group-introduced pulp thus prepared are not particularly limited, but are, for example, as follows.

[0063] <Amount of sulfate ester group introduced> The amount of sulfate ester groups introduced per 1 g (solid mass) of sulfate ester group-introduced pulp is preferably adjusted to, for example, 0.6 mmol / g or more, 0.8 mmol / g or more, 1 mmol / g or more, or 1.2 mmol / g or more.

[0064] Incidentally, the upper limit is not particularly limited, but from the viewpoint of suppressing fiber collapse and cost increase caused by decreased crystallinity, for example, the amount of sulfate ester groups introduced per 1 g (solid content mass) of sulfate ester group-introduced pulp is 9.9 mmol / g or less, 5 mmol / g or less.

[0065] From the viewpoint of viscosity, the sulfate ester group-introduced pulp is preferably prepared as follows. By setting the amount of sulfate ester groups per 1 g (solid content mass) of sulfate ester group-introduced pulp within the following range, a decrease in viscosity in the dispersion can be suppressed. For example, the upper limit of the amount of sulfate ester groups per 1 g (solid content mass) of sulfate ester group-introduced pulp is 3.5 mmol / g or less, 2 mmol / g or less. The lower limit is, for example, 0.6 mmol / g or more, 1 mmol / g or more, 1.5 mmol / g or more. For example, in the sulfate ester group-introduced pulp, the amount of sulfate ester groups per 1 g (solid content mass) of sulfate ester group-introduced pulp can be adjusted to 0.6 mmol / g to 3.5 mmol / g, 1 mmol / g to 2.5 mmol / g, or 1.5 mmol / g to 2 mmol / g.

[0066] The dispersion medium constituting the dispersion liquid of the sulfate ester group-introduced pulp is not particularly limited, but is preferably one that can exhibit the above-mentioned viscosity, etc. For example, the dispersion medium may be a protic polar solvent such as water, ethanol, methanol, acetic acid, formic acid, 2-propanol, nitromethane, or ammonia water, an aprotic polar solvent such as acetone, ethyl acetate, tetrahydrofuran (THF), dimethylformamide (DMF), acetonitrile, dimethyl sulfoxide (DMSO), dimethyl sulfide (DMS), or dimethylacetamide (DMA), or a non-polar solvent such as dimethyl ether, benzene, toluene, hexane, chloroform, or 1,4-dioxane, and one of these may be used alone, or two or more may be used in combination. From the viewpoint of handling, for example, a protic polar solvent such as water, ethanol, methanol, acetic acid, formic acid, or ammonia water may be used.

[0067] <Method for measuring the amount of sulfate ester groups introduced> The amount of sulfate ester groups introduced into the sulfate ester group-introduced pulp can be evaluated based on the amount of sulfur introduced due to the sulfate ester groups, or by directly measuring the sulfate ester groups. For example, the amount of sulfate ester groups introduced into the pulp can be measured using a CHNS / O elemental analyzer. The amount of sulfate ester groups introduced into the pulp can also be calculated by measuring electrical conductivity.

[0068] <Crystallization degree> The sulfate ester group-introduced pulp may have, for example, a cellulose I type crystal structure as a crystal structure, and the degree of crystallinity may be 75% or less. From the viewpoint of maintaining the fiber shape, the degree of crystallinity of the sulfate ester group-introduced pulp is preferably 30% or more. From the viewpoint of viscosity, the degree of crystallinity of the sulfate ester group-introduced pulp is, for example, 70% or less, 65% or less, or 60% or less. Furthermore, from the viewpoint of handleability in the method for preparing the sulfate ester group-introduced pulp, the degree of crystallinity of the sulfate ester group-introduced pulp is, for example, 30% or more, or 40% or more.

[0069] <Method for measuring crystallinity> The crystallinity of the sulfate ester group-introduced pulp can be measured, for example, by using an X-ray diffraction device.

[0070] The sulfate ester group-introduced pulp has an excellent viscosity due to, for example, a predetermined degree of crystallinity. Specifically, the viscosity of a pulp having a general I-type crystal structure is about several tens to several hundreds of mPa·s when measured by rotating at 6 rpm at 20°C for 3 minutes using a B-type viscometer, whereas the sulfate ester group-introduced pulp can exhibit an excellent viscosity (for example, several thousand mPa·s or more) that was not expected for conventional general pulps.

[0071] <Average fiber length> The average fiber length of the sulfate ester group-introduced pulp is not particularly limited, and is, for example, 0.2 mm to 2 mm, 0.2 mm to 1.8 mm, 0.2 mm to 1.5 mm, or 0.2 mm to 1 mm.

[0072] <Short fiber rate (%)> The sulfate ester group-introduced pulp may also contain pulp with short fiber length as described below. Examples of this pulp with short fiber length (hereinafter referred to as "short fiber") include pulp with a fiber length of 0.04 mm or more and 0.2 mm or less in the fiber length distribution. The content (%) of short fibers in the sulfate ester group-introduced pulp (i.e., short fiber rate (%)) is, for example, 10% or more, 15% or more.

[0073] From the viewpoint of handleability, the sulfate ester group-introduced pulp has a short fiber content (%) (i.e., short fiber rate (%)) of, for example, 10% to 70%, 10% to 60%, 10% to 50%, 10% to 45%, or 15% to 45% in terms of fiber length distribution.

[0074] <Average fiber width> The average fiber width of the sulfate ester group-introduced pulp is not particularly limited, and is, for example, 5 μm to 100 μm, 10 μm to 50 μm, 20 μm to 40 μm, or 20 μm to 30 μm.

[0075] <Measuring methods for average fiber length, average fiber width and fiber distribution> The average fiber length and average fiber width of the sulfate ester group-introduced pulp can be measured, for example, using a fiber tester or fiber length distribution measuring instrument manufactured by Lorentzen & Wettley in accordance with ISO16065-2: 2007. The fiber length distribution and fiber width distribution of the sulfate ester group-introduced pulp can be measured, for example, using a fiber length distribution measuring instrument in accordance with ISO16065-2: 2007.

[0076] <Viscosity> When the degree of crystallinity of the sulfate ester group-introduced pulp is equal to or less than the aforementioned value, for example, the dispersion has a predetermined viscosity. For example, when the degree of crystallinity of the sulfate ester group-introduced pulp is 70% or less, the viscosity of the dispersion (solid content concentration 1% by mass) in which the sulfate ester group-introduced pulp is dispersed in water is 1000 mPa·s or more, 5000 mPa·s or more, or 10000 mPa·s or more. In particular, when the degree of crystallinity of the sulfate ester group-introduced pulp is 60% or less, the viscosity of the dispersion tends to increase. Furthermore, when the average fiber length is 1 mm or less, this tendency becomes stronger.

[0077] <Method of measuring viscosity> The viscosity (mPa s) of the sulfate ester group-introduced pulp can be measured, for example, using a B-type viscometer at a measurement temperature of 20°C, with the measurement performed at rotation speeds of 6 rpm and 60 rpm. The thixotropy index (TI) can also be calculated from each viscosity value. TI value = (viscosity at 6 rpm) / (viscosity at 60 rpm)

[0078] The TI value can be adjusted as appropriate, and when a high TI value is required, the lower limit of the TI value is, for example, 3 or more, 4 or more, or 5 or more. The upper limit of the TI value is, for example, 10 or less, 8 or less, 6 or less, or 5 or less. On the other hand, when a low TI value is preferred, the lower limit is, for example, 1 or more, and the upper limit is, for example, 3 or less, or 2.5 or less.

[0079] <Method for preparing fine cellulose fiber> The fine cellulose fibers can be obtained by subjecting the sulfate ester group-introduced pulp prepared as described above to a fine pulp refining treatment step.

[0080] <Micronization process> The micronization step of this method is a step of micronizing the sulfate ester group-introduced pulp to produce fine fibers of a predetermined size (for example, nano-level). The processing device used in this micronization step is not particularly limited as long as it has the above-mentioned function. For example, the processing device may be, but is not limited to, a low-pressure homogenizer, a high-pressure homogenizer, a grinder (stone-type grinder), a ball mill, a cutter mill, a jet mill, a single-screw extruder, a twin-screw extruder, an ultrasonic agitator, a household mixer, etc. Among these, it is desirable to use a high-pressure homogenizer, since it can apply force evenly to the material and is excellent in homogenization.

[0081] In the case where a high-pressure homogenizer is used in the microparticulation process, the sulfate ester group-introduced pulp is supplied in a state of being dispersed in an aqueous dispersion medium such as water. In the following, the dispersion liquid in which the sulfate ester group-introduced pulp is dispersed may be referred to as a slurry. The solid content concentration of the sulfate ester group-introduced pulp in this slurry is not particularly limited, and is, for example, 0.1% by mass to 20% by mass.

[0082] For example, if a slurry in which the solid content of sulfate ester group-introduced pulp has been adjusted to 0.5% by mass is fed to a processing device such as a high-pressure homogenizer, a dispersion liquid in which fine cellulose fibers having the same solid content are dispersed in an aqueous dispersion medium can be obtained. That is, in this case, a dispersion liquid with a solid content of 0.5% by mass can be obtained.

[0083] In addition, the water retention of the sulfate ester group-introduced pulp to be subjected to the fine processing step is not particularly limited, but is preferably adjusted so as to be easily fined by the above-mentioned device or the like. For example, from the viewpoint of the processing efficiency of fine processing and the reduction of energy used, it is desirable to use sulfate ester group-introduced pulp prepared to have a high water retention. From this viewpoint, it is preferable to use sulfate ester group-introduced pulp prepared to have a water retention of 150% or more, 200% or more, 250% or more, 300% or more, or 500% or more. From the viewpoint of the recovery rate of fine cellulose fibers, the water retention is, for example, 10000% or less. Thus, from the viewpoint of the fine processing efficiency and the recovery rate, the water retention of the sulfate ester group-introduced pulp to be subjected to the fine processing step is 150% to 10000%, 200% to 10000%, 220% to 10000%, 250% to 5000%, or 250% to 2000%.

[0084] The amount of the fine cellulose fibers in the total amount of the composition is, for example, 0.0005% by mass to 0.5% by mass. As described later, when the composition is for spraying (composition for spraying), the amount of the fine cellulose fibers is increased to suppress dripping during spraying (spraying). For example, when the composition is used for cleaning a toilet, if the composition remains in place without dripping during spraying (spraying), it is considered that an antifouling effect is easily obtained. On the other hand, when it is desired to drip from the spraying (spraying) site and spread it downward, the amount of the fine cellulose fibers may be reduced. The dripping can be adjusted, for example, by adding other components such as a surfactant described later.

[0085] (water) The water is preferably ion-exchanged water or pure water. The amount of water in the total amount of the composition may be, for example, the remainder of the other components.

[0086] (Disinfectant) The composition may further contain a disinfectant. Examples of the disinfectant include 2,2-dibromo-2-nitroethanol, 2-bromo-2-nitropropane-1,3-diol, 2,2-dibromo-3-nitrilopropionamide, benzoic acid, dehydroacetic acid, sorbic acid, paraoxybenzoic acid esters, butylhydroxyanisole, butylhydroxytoluene, and ethanol. The disinfectant may be used alone or in combination of two or more. The disinfectant exemplified above may also function as a preservative.

[0087] When the composition is used for cleaning a toilet, the disinfectant preferably contains one or more of 2,2-dibromo-2-nitroethanol, 2-bromo-2-nitropropane-1,3-diol, and 2,2-dibromo-3-nitrilopropionamide. These disinfectants have a urease inhibitory effect, and therefore can suppress the generation of ammonia caused by the decomposition of urea in urine scattered on the floor, wall, and inner rim of the toilet bowl by the urease enzyme of microorganisms. In addition, as a result of suppressing the generation of ammonia due to the enzymatic decomposition of urea, the growth of alkaline metal scale caused by alkaline earth metals and silicates due to the increase in pH caused by the generation of ammonia can also be suppressed. Furthermore, the disinfectants exemplified above can disinfect ammonia-producing bacteria such as Pseudomonas aeruginosa, which produces urinary stones and biofilms.

[0088] The blending amount of the disinfectant in the total amount of the composition is, for example, 0.005% by mass to 0.5% by mass, 0.01% by mass to 0.1% by mass, or 0.05% by mass to 0.1% by mass.

[0089] (Surfactant) The composition may further contain a surfactant. Examples of the surfactant include a nonionic surfactant, an amphoteric surfactant, an anionic surfactant, and a cationic surfactant. The surfactant may be used alone or in combination of two or more kinds.

[0090] <Nonionic surfactant> Examples of the nonionic surfactant include (decyl, octyl) glycoside of D-glucopyranose oligomer, polyoxyalkylene (number of moles added: 1 to 50 moles) alkyl (carbon number: 6 to 18) ether, polyoxyalkylene (number of moles added: 1 to 50 moles) acyl (carbon number: 6 to 18) ester, alkyl (carbon number: 6 to 18) diethanolamide, polyoxyalkylene (number of moles added: 1 to 100 moles) triglyceride (fatty acid carbon number: 6 to 18) ether, sorbitan fatty acid (carbon number: 6 to 18) ester, sucrose fatty acid (carbon number: 6 to 18) ester, polyoxyalkylene (number of moles added: 1 to 50 moles) sorbitan fatty acid (carbon number: 6 to 18) ester, alkyl (carbon number: 6 to 18) polyglycoside, polyoxyethylene polyoxypropylene block polymer, and the like.

[0091] <Amphoteric surfactant> Examples of the amphoteric surfactant include sodium alkyldi(aminoethyl)glycine, alkyldiaminoethylglycine hydrochloride, alkyl (C6-18) betaine, fatty acid (C6-18) amidopropyl betaine, 2-alkyl(C6-18)-N-carboxymethyl-N-hydroxyethyl-imidazolinium betaine, alkyl(C6-18) diethylenetriaminoacetic acid, dialkyl(C6-18) diethylenetriaminoacetic acid, alkyl(C6-18) amine oxide, and the like.

[0092] <Anionic surfactant> Examples of the anionic surfactant include alkyl (having 10 to 15 carbon atoms) benzenesulfonates, alkyl (having 6 to 18 carbon atoms) sulfates, polyoxyalkylene (number of moles added: 1 to 30 moles) alkyl (having 6 to 18 carbon atoms) ether sulfates, alkane (having 6 to 18 carbon atoms) sulfonates, olefin (having 8 to 18 carbon atoms) sulfonates, naphthalenesulfonate condensates, alkyl (having 6 to 18 carbon atoms) sulfosuccinates, polyoxyalkylene (number of moles added: 1 to 30 moles) alkyl (having 6 to 18 carbon atoms) ether sulfosuccinates, alkyl (having 6 to 18 carbon atoms) phosphates, polyoxyalkylene (number of moles added: 1 to 30 moles) alkyl (having 6 to 18 carbon atoms) ether phosphates, polyoxyalkylene (number of moles added: 1 to 30 moles) alkyl (having 6 to 18 carbon atoms) ether acetates, and the like. Examples of the salt include salts of alkali metals such as sodium and potassium, salts of alkaline earth metals such as calcium and magnesium, and salts of amines such as ammonia and alkanolamines.

[0093] <Cationic surfactant> Examples of the cationic surfactant include monoalkyl (having 6 to 18 carbon atoms) amine salts, dialkyl (having 6 to 18 carbon atoms) amine salts, trialkyl (having 6 to 18 carbon atoms) amine salts, alkyl (having 6 to 18 carbon atoms) trimethylammonium salts, dialkyl (having 6 to 18 carbon atoms) dimethylammonium salts, alkyl dimethylbenzylammonium salts, and alkyl (having 6 to 18 carbon atoms) dimethylaminopropylamides.

[0094] When the composition is used for cleaning a toilet, the surfactant preferably contains at least one of sodium alkyldi(aminoethyl)glycine and alkyldiaminoethylglycine hydrochloride, which are amphoteric surfactants. These are amphoteric surfactants with disinfecting and cleaning effects, and have a high disinfecting effect against fungi such as mold and yeast and imperfect fungi, so that they can suppress the generation of odors derived from ammonia and metabolic products that are naturally generated as a result of the catabolism of organic matter by fungi and imperfect fungi. In addition, these amphoteric surfactants can penetrate into metal scale and soft scale due to their surfactant effect and disinfect the bacteria living inside the scale, so that they can suppress the growth of scale. Furthermore, these amphoteric surfactants contribute to the cleaning and removal of organic matter, so that if they are used in combination with a disinfectant having the above-mentioned urease inhibitory effect and disinfecting effect, the decrease in the effect due to the remaining organic matter can be suppressed.

[0095] The amount of the surfactant in the total amount of the composition is, for example, 0.01% by mass to 4% by mass, or 0.01% by mass to 1.5% by mass.

[0096] (fragrance) The composition may further contain a fragrance. When the composition contains the fine cellulose fibers, the composition can improve the dispersibility of a fragrance when the fragrance is contained, and can exhibit an excellent deodorizing effect.

[0097] The fragrance is not particularly limited, and examples thereof include synthetic fragrance compounds, natural oils, and blended fragrances prepared therefrom, such as peppermint, jasmine, bouquet, rose, lily of the valley, aldehyde, green, citrus, woody, animal, fruity, spice, etc. The fragrance may be used alone or in combination of two or more.

[0098] The blending amount of the fragrance in the total amount of the composition is, for example, 0.001% by mass to 1% by mass.

[0099] (pH adjuster) The composition may further include a pH adjuster. Examples of the pH adjuster include an acid or an alkali. Whether the composition is acidic or alkaline depends on the use of the composition, and it is appropriate to determine whether to use an acid or an alkali accordingly. For example, when the composition is used to clean oil stains, it is appropriate to make the composition alkaline, and therefore an alkali may be used as the pH adjuster.

[0100] Examples of the acid include organic acids such as citric acid, lactic acid, oxalic acid, tartaric acid, and gluconic acid, and inorganic acids such as phosphoric acid. The acid may be used alone or in combination of two or more. When the composition is used for cleaning a toilet, the acid may also have the effect of removing urinary stones, limescale, and dirt caused by splashes of urine and water, inhibiting scale, and reducing ammonia odor.

[0101] Examples of the alkali include organic alkalis such as alkanolamines, inorganic alkalis such as sodium carbonate, etc. The alkalis may be used alone or in combination of two or more.

[0102] The amount of the pH adjuster in the total amount of the composition is, for example, 0.01% by mass to 10% by mass, or 0.05% by mass to 0.2% by mass.

[0103] The composition can be prepared, for example, by uniformly mixing the disinfectant, the surfactant, the fine cellulose fibers, the water, and, if necessary, other additive components, by a conventionally known method.

[0104] When the composition is used for flushing a toilet, the pH of the composition is preferably 3 or more and less than 5. In this case, the composition is weakly acidic. The pH of the composition may be adjusted using the above-mentioned acid (pH adjuster). When the composition is made weakly acidic using the above-mentioned acid, in addition to the effects of removing the above-mentioned urinary stones, limescale, and stains caused by urine and water splashes, inhibiting scale, and reducing ammonia odor, the composition is safer than a strong acid such as hydrochloric acid, is less likely to cause rough skin when it comes into contact with the skin, and does not damage the fine cellulose fibers contained in the composition.

[0105] [Embodiment 2: Spray device] The composition of the present invention may be for spray use (spray composition). The spray device of the present invention is filled with the above-mentioned spray composition of the present invention.

[0106] The spray device is preferably one that can easily be filled with the spray composition of the present invention, and examples of the spray device include a dispenser type spray device equipped with a pump nozzle, a trigger type spray device, and an aerosol type spray device.

[0107] Dispenser-type spray devices equipped with pump nozzles can spray at atmospheric pressure, do not require pressurized gas, and have a simple structure, making them highly safe and suitable for portability. The structure includes an extrusion pump nozzle equipped with a suction tube, and a screw-type container to which the nozzle is fixed and into which the contents are filled.

[0108] A trigger-type spray device is a device in which a pistol-shaped trigger-type sprayer is attached to the mouth of a container body into which the contents are filled, and which can operate the spray at atmospheric pressure and is highly versatile.

[0109] The aerosol spray device fills a container with a propellant, enabling continuous spraying that is difficult to achieve with the two spray devices. The propellant is not particularly limited, and examples thereof include dimethyl ether, liquefied petroleum gas, carbon dioxide gas, nitrogen gas, argon gas, air, oxygen gas, and fluorocarbon gas. The propellant may be used alone or in combination of two or more types.

[0110] The use of the composition and spray device of the present invention is not particularly limited, and may be used, for example, as a cleaning agent for commercial or household use. Specifically, the composition and spray device of the present invention may be used for a variety of purposes, for example, as a toilet cleaner, a bathroom cleaner, a kitchen cleaner, etc. In particular, when used as a toilet cleaner, the entire toilet can be cleaned by using only the composition or spray device of the present invention. EXAMPLES

[0111] (Examples 1-1 to 1-5) The compositions of Examples 1-1 to 1-5 shown in Table 1 were obtained by uniformly mixing the components of the composition (Table 1).

[0112] [Table 1]

[0113] The fine cellulose fibers in Table 1 were prepared as follows.

[0114] (Preparation of sulfate ester group-introduced pulp) Softwood kraft pulp (NBKP) (hereinafter, simply referred to as "pulp") with an average fiber length of 2.54 mm manufactured by Marusumi Paper Co., Ltd. was washed with a large amount of ion-exchanged water, and then the water was drained using a sieve with an opening of 75 μm (200 mesh). The solid content of a part of the pulp thus obtained was measured, and it was 21.6 mass%. As the ion-exchanged water, water with an electric conductivity of 0.1 μS / cm to 0.2 μS / cm measured with an ion-exchanged water generator (model number: G-5DSTEST) manufactured by Organo Co., Ltd. was used, and hereafter, this is referred to as pure water. Thereafter, the wet pulp was spread on an aluminum tray, placed in a dryer under an atmosphere of 105°C, and dried for about 1 hour until the moisture content reached about 1%.

[0115] <Contact process> 1000 g of the reaction solution was added to 20 g of pulp (solid content mass), and the reaction solution was impregnated into the pulp. The reaction solution used was an aqueous solution in which sulfamic acid and urea were mixed at a concentration ratio (g / L) of sulfamic acid:urea=2:1 (180 g / L:90 g / L). The sulfamic acid used was a product of Fuso Chemical Co., Ltd. with a purity of 99.8%, and the urea used was a product of Fujifilm Wako Pure Chemical Co., Ltd. with a purity of 99.0%, model number: special grade reagent.

[0116] The pulp impregnated with the reaction solution was dehydrated by suction filtration and spread on an aluminum tray. The aluminum tray was then placed in a dryer in an atmosphere of 80°C and dried to prepare reaction solution impregnated pulp. The moisture content of the reaction solution impregnated pulp was 5% or less. Filter paper (manufactured by Advantech, model number: No. 2) was used for the suction filtration.

[0117] <Reaction process> The reaction liquid-impregnated pulp was subjected to a heating reaction using a dryer. The temperature of the thermostatic chamber of the dryer was 140°C, and the heating time was 30 minutes. The reaction liquid-impregnated pulp after heating was washed until it became neutral, to prepare a sulfate ester group-introduced pulp having an introduction amount of 1.39 mmol / g of sulfate ester groups. The washing was performed by adding a large amount of pure water to the reaction liquid-impregnated pulp to make a slurry, and then neutralizing it by adding sodium bicarbonate (manufactured by Nacalai Tesque, Inc., purity 99.5%) until no bubbles were generated.

[0118] (Preparation of fine cellulose fibers) The sulfate ester group-introduced pulp was subjected to defibration treatment five times using a high-pressure homogenizer (Yoshida Kikai Kogyo Co., Ltd., "Nano-Veita", pressure: 60 MPa) to prepare a dispersion of 1.05% by mass of fine cellulose fibers.

[0119] [Anti-soiling and stain removal tests] The compositions of Examples 1-1 to 1-5 were colored with Brilliant Blue FCF (food blue No. 1), 1 mL of each was dropped onto an ABS resin plate, and then allowed to stand for 24 hours. Then, about 0.5 g of confectionery chocolate and honey were dropped onto the dropped and non-dropped portions of the compositions, and allowed to stand for 1 hour.

[0120] Thereafter, the plate surface was washed with running tap water, and the degree of removal of the confectionery chocolate and honey was visually confirmed. As a result, in the dripped parts of the compositions of Examples 1-4 and 1-5, the dried and attached compositions peeled off together and flowed off without a trace. In the dripped parts of the compositions of Examples 1-3, the compositions gradually peeled off and flowed off. In the dripped parts of the compositions of Examples 1-1 and 1-2, the compositions similarly flowed off, but a small amount of confectionery chocolate was observed to remain. On the other hand, in the non-dripped parts, the honey flowed off, but the confectionery chocolate was almost entirely left. In addition, in the non-dripped parts and the dripped parts of the compositions of Examples 1-1 to 1-3, traces of the chocolate that had flowed off were observed on the plate surface, and the amount of the traces was greater as the blending amount of fine cellulose fibers was smaller. In this way, it was confirmed that the parts to which the compositions of Examples 1-1 to 1-5 were attached were less likely to get dirty and were easy to remove.

[0121] Next, the ABS resin plate was roughened with sandpaper (120), and tests were conducted in the same manner as described above, except that only chocolate for confectionery was used without using honey. As a result, in the dripped parts of the compositions of Examples 1-2 to 1-5, the dried and attached compositions peeled off together and flowed off without a trace. In the dripped parts of the composition of Example 1-1, some of the chocolate for confectionery remained, and in the non-dripped parts, the chocolate for confectionery remained almost entirely. Thus, it was confirmed that even on the rough surface of the resin plate, the parts to which the compositions of Examples 1-1 to 1-5 were attached were resistant to staining and easy to remove. In this stain prevention and stain removal test, the compositions were dripped in consideration of repelling by the resin plate, but it was confirmed that these compositions can be sprayed (sprayed) with a spray device, and similar results can be obtained even when sprayed.

[0122] (Examples 2-1 to 2-5, 3-1 to 3-5, 4-1 to 4-5, 5-1 to 5-5, and 6-1 to 6-3) The components of the composition (Tables 2 to 6) were mixed uniformly to obtain compositions of Examples 2-1 to 2-5, 3-1 to 3-5, 4-1 to 4-5, 5-1 to 5-5, and 6-1 to 6-3 shown in Tables 2 to 6. The fine cellulose fibers in Tables 2 to 6 were prepared in the same manner as the fine cellulose fibers in Table 1. In Tables 2 to 6, the pH indicates the pH value of the composition of each Example.

[0123] [Table 2]

[0124] [Table 3]

[0125] [Table 4]

[0126] [Table 5]

[0127] [Table 6]

[0128] [Third-party evaluation] A third party was asked to use a dispenser-type spray device equipped with a pump nozzle filled with the composition shown in Tables 2 to 6 to clean the toilets in the store. As a result, the third party evaluated that odor and dirt were reduced, and that the entire toilet could be cleaned with just the spray device, making cleaning easier.

[0129] [Anti-fouling performance verification test] 0.5 mL of each of the compositions shown in Tables 2 to 6 was dropped onto a white ABS resin plate, left to stand for 24 hours, and allowed to dry naturally. After that, the area above the drop was filled in with a black oil-based marker (Zebra Co., Ltd.'s Makie) in a stripe shape, and then wiped off with tissue paper while rinsing with tap water. The results are shown in Figure 1.

[0130] As shown in Fig. 1, peeling of the oil-based marker was observed at the drop portion of the composition of each example, and peeling of the oil-based marker was observed more frequently as the blending amount of the fine cellulose fiber increased. In particular, at the drop portion of the compositions of Examples 2-4, 2-5, 3-4, 3-5, 4-4, 4-5, 5-4, 5-5, and 6-1 to 6-3, in which the blending amount of the fine cellulose fiber was 0.1 mass% or more, almost all of the oil-based marker was peeled off, confirming high antifouling performance.

[0131] [Cleanliness measurement using a Lumitester] The cleanliness after 1 mL of dairy lactic acid bacteria beverage (Y1000 (containing 110 billion Lactobacillus casei strain YIT 9029) manufactured by Yakult Honsha Co., Ltd.) was applied to the ABS resin plate was evaluated by reacting ATP (adenosine triphosphate) contained in bacteria and microorganisms with luciferase, an enzyme derived from fireflies, to cause light emission, and measuring the amount of light emitted with a Lumitester. As a result of measurement with a Lumitester, the value of the ABS resin plate after washing and drying was 0 RLU, and the value after applying 1 mL of the dairy lactic acid bacteria beverage was 10,061 RLU. The values ​​after spraying the applied area five times (spray amount about 1 mL) with a dispenser-type spray device equipped with a pump-type nozzle filled with water (comparative example) or a part of the composition shown in Tables 2 to 6, and wiping it off five times in one direction with a paper towel were as shown in Table 7. The measured values ​​of each example and comparative example shown in Table 7 are the average values ​​of measurements performed three times.

[0132] [Table 7]

[0133] As shown in Table 7, when the compositions of any of the Examples were sprayed, the values ​​were significantly lower than when water was sprayed as the Comparative Example, demonstrating an excellent dirt removal effect.

[0134] [Ammonia deodorization test] A 2.5 cm x 2.5 cm piece of nonwoven fabric placed in a plastic bag (Ziploc (registered trademark) made by Asahi Kasei Home Products Corp.) was soaked with 0.25 mL of ammonia water colored blue with a pH indicator, and the ammonia concentration was measured by the Kitagawa detector tube method (initial concentration measurement). After the initial concentration measurement, water (Comparative Example) or a composition shown in Tables 2 to 6 was added until the pH indicator changed from blue (alkaline) to yellow (acidic), and then the ammonia concentration was measured by the Kitagawa detector tube method. The results are shown in Table 8. The measured values ​​for each Example and Comparative Example shown in Table 8 are the average values ​​of measurements performed five times.

[0135] [Table 8]

[0136] As shown in Table 8, when water was added as a comparative example, the ammonia concentration decreased from 12 ppm to 9 ppm, whereas when any of the compositions of the examples were added, the ammonia concentration fell below the detection limit, confirming that an ammonia deodorizing effect was obtained.

[0137] (Examples 7-1 to 7-3) The compositions of Examples 7-1 to 7-3 were obtained by uniformly mixing the components of the composition (Table 9). The fine cellulose fibers in Table 9 were prepared in the same manner as the fine cellulose fibers in Table 1. In Table 9, the pH indicates the pH value of the composition of each Example.

[0138] [Table 9]

[0139] [Ammonia deodorization test] The ammonia deodorization test was carried out in the same manner as described above for the compositions of Examples 7-1 to 7-3 shown in Table 9. The results are shown in Table 10. The measured values ​​for each Example shown in Table 10 are the average values ​​of measurements taken three times.

[0140] [Table 10]

[0141] As shown in Table 10, it was confirmed that the addition of the compositions of Examples 7-1 to 7-3 also reduced the ammonia concentration to below the detection limit, and an ammonia deodorizing effect was obtained.

[0142] [Anti-fouling performance verification test] The antifouling performance confirmation test was carried out in the same manner as described above for the compositions of Examples 7-1 to 7-3 shown in Table 9. The results are shown in FIG.

[0143] As shown in FIG. 2, peeling of the oil-based marker was observed where the composition of each Example was dropped, and peeling of the oil-based marker was observed more frequently as the blending amount of fine cellulose fibers was increased.

[0144] (Examples 8-1 to 8-7) The compositions of Examples 8-1 to 8-7 were obtained by uniformly mixing each component of the composition (Table 11). The fine cellulose fibers in Table 11 were prepared in the same manner as the fine cellulose fibers in Table 1. The compositions of Examples 8-1 and 8-3 have the same composition as the compositions of Examples 2-4 and 2-5 shown in Table 2, but were prepared separately for the dripping test described below.

[0145] [Table 11]

[0146] [Drip test] The compositions of Examples 8-1 to 8-7 were colored with Brilliant Blue FCF (food blue No. 1), and 10 μL, 15 μL, 20 μL, 25 μL, 30 μL, or 35 μL of each was dropped onto the edge of a white ABS resin plate (247 mm × 332 mm). Then, the ABS resin plate was slowly turned vertically so that the edge onto which the composition was dropped was facing up, and left to stand for 1 minute, after which the degree of dripping was visually confirmed. The results are shown in FIG. 3. In FIG. 3, the ones with almost no or moderate dripping are surrounded by a dashed square, and the ones with a large degree of dripping are surrounded by a solid square. The compositions were dropped using a Finn pipette F3 10-100 μL manufactured by Thermo Fisher Scientific.

[0147] As shown in Fig. 3(A), when the amount of dripping was 10 μL, some dripping was observed in Example 8-2, but no dripping was observed in Examples 8-1 and 8-3 to 8-7, and the composition remained at the dripped portion as it was. Also, as shown in Fig. 3(B), when the amount of dripping was 15 μL, dripping was observed in Examples 8-1 to 8-3, and the composition flowed down to the other end of the ABS resin plate, whereas no dripping was observed in Examples 8-4 to 8-7, and the composition remained at the dripped portion as it was. And, as shown in Fig. 3(C) and Fig. 3(D), when the amount of dripping was 20 μL or 25 μL, dripping was observed in Examples 8-1 to 8-5, and the composition flowed down to the lower part or the other end of the ABS resin plate, whereas no dripping was observed in Examples 8-6 and 8-7, and the composition remained at the dripped portion as it was. Furthermore, as shown in FIG. 3(E), in the case where only Examples 8-6 and 8-7 were performed with a dripping amount of 30 μL, some dripping was observed in Example 8-6, but no dripping was observed in Example 8-7, and the composition remained at the dripping portion as it was. On the other hand, as shown in FIG. 3(F), in the case where only Examples 8-6 and 8-7 were performed with a dripping amount of 35 μL, dripping was observed in Example 8-6, and the composition flowed down to the other end of the ABS resin plate, whereas no dripping was observed in Example 8-7, and the composition remained at the dripping portion as it was. In this way, it was confirmed that the degree of dripping can be adjusted by the blending amount of the fine cellulose fiber in the composition. In this dripping test, the composition was dripped taking into consideration the repelling by the resin plate, but it was confirmed that these compositions can be sprayed (sprayed) with a spray device, and it is considered that similar results can be obtained when sprayed.

Claims

1. Contains fine cellulose fibers and water, A composition, wherein at least a portion of the hydroxyl groups of the fine cellulose fibers are substituted with sulfate ester groups.

2. The composition of claim 1 , further comprising a disinfectant and a surfactant.

3. The composition according to claim 1 or 2, further comprising a fragrance.

4. The composition according to any one of claims 1 to 3, further comprising a pH adjuster.

5. The composition according to any one of claims 1 to 4, having a pH of 3 or more and less than 5.

6. The composition according to any one of claims 1 to 5, which is for spray application.

7. A spray device filled with the composition of claim 6.

Citation Information

Patent Citations

  • cleaning products

    JP2022078252A

  • Sprayable cleaning composition

    JP2022088549A